2020
DOI: 10.1017/asb.2020.12
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Insurance Contracts Under Distortion Risk Measures With Ambiguity Aversion

Abstract: This paper presents analytical representations for an optimal insurance contract under distortion risk measure and in the presence of model uncertainty. We incorporate ambiguity aversion and distortion risk measure through the model of Robert and Therond [(2014) ASTIN Bulletin: The Journal of the IAA, 44(2), 277–302.] as per the framework of Klibanoff et al. [(2005) A smooth model of decision making under ambiguity. Econometrica, 73(6), 1849–1892.]. Explicit optimal insurance indemnity functions are derived wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Often being a critical issue in insurance practice, model uncertainty has received increasing attention in the insurance literature. The following works, among others, have investigated or touched this issue in various insurance contexts: Cairns (2000), Chen and Su (2009), Peters et al (2009), Zhao and Zhu (2011) , Landsman and Tsanakas (2012), Robert and Therond (2014), Liu and Wang (2017), Fujii et al (2017), and Jiang et al (2020). More applications to practical problems in insurance have been proposed during recent years but are still sporadic; see Wozabal (2014), Pflug et al (2017), Lam and Mottet (2017), Asimit et al (2017Asimit et al ( , 2019, Ghossoub (2019aGhossoub ( , 2019b, , Pflug (2019), andBirghila et al (2020), among others.…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Often being a critical issue in insurance practice, model uncertainty has received increasing attention in the insurance literature. The following works, among others, have investigated or touched this issue in various insurance contexts: Cairns (2000), Chen and Su (2009), Peters et al (2009), Zhao and Zhu (2011) , Landsman and Tsanakas (2012), Robert and Therond (2014), Liu and Wang (2017), Fujii et al (2017), and Jiang et al (2020). More applications to practical problems in insurance have been proposed during recent years but are still sporadic; see Wozabal (2014), Pflug et al (2017), Lam and Mottet (2017), Asimit et al (2017Asimit et al ( , 2019, Ghossoub (2019aGhossoub ( , 2019b, , Pflug (2019), andBirghila et al (2020), among others.…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
“…(2017), and Jiang et al . (2020). More applications to practical problems in insurance have been proposed during recent years but are still sporadic; see Wozabal (2014), Pflug et al .…”
Section: Introductionmentioning
confidence: 99%
“…In a related work, Jiang et al. (2020) derived the explicit optimal insurance indemnity functions when the decision maker applies value‐at‐risk as risk measure and found that a more ambiguity‐averse decision maker would demand more insurance coverage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More such examples of optimal reinsurance that can be written of the form of (2.4) can be found in Assa (2015) , Boonen, Tan, & Zhuang (2016) , Asimit & Boonen (2018) , Lo & Tang (2019) . In the presence of model ambiguity, we refer the interested readers to Hansen & Sargent (2011) for many basic and advanced techniques in robust decision making, and Birghila & Pflug (2019) , Birghila, Boonen, &Ghossoub (2020) , andJiang, Escobar-Anel, &Ren (2020) for some recent advances on robust insurance contracting. In the next subsection, we present the main problem to be addressed in this paper.…”
Section: Other Specific Problems With the Form (24)mentioning
confidence: 99%